Emotions inspire transformation: delving into EFL teachers’ emotions and professional identities - Dağtaş, Aysun; Zaimoğlu, Senem (Frontiers in Education, 2025)
Emotions are increasingly recognized as central to the teaching and learning process, particularly in the context of language education. This study aimed to explore the intricate relationship between emotional experiences of language teachers and their evolving professional identities. Drawing on the theoretical frameworks of teacher emotions and identity, the research addresses the shift from cognitive to sociocultural and critical perspectives in studies about language teachers’ emotions. Situated in a Turkish university context, the study involved semi-structured interviews and narratives from seven English language teachers. Participants shared insights into their emotional experiences, professional development, and challenges encountered in institutional and cultural settings. Thematic reflexive analysis revealed three main themes: (1) navigating emotional diversity, (2) dealing with emotional diversity and regulation, and (3) emotional alignment. The results revealed the complex and dialogic nature of the relationship between teacher emotions and identity, which points the need for emotionally supportive professional environments. This study contributes to a broader understanding of identity work as an emotional process, offering implications for teacher education and well-being in language teaching contexts.